Estudo comparativo da desadaptação marginal de infraestruturas metálicas para próteses sobre implantes, após soldagem a laser e soldagem convencional - Peçanha, Marcelo Massaroni (2009)
The aim of this study is to compare the marginal inaccuracy of Co-Cr implantsupported frameworks after conventional soldering or laser welding procedures. Two externally hexed implants with 4.1 mm platform diameter (Conexão Sistema de Prótese,Brazil) were fixed in an aluminum block. The framework wax-up was produced using two Co-Cr UCLA cylinders positioned in each implant and a pre-fabricated wax bar. The implant frameworks were conventionally casted using Co-Cr alloy. Twenty frameworks were produced sectioned in two halves and assigned to two different groups: in Group 1 frameworks were re-joined using laser-welded and in group 2 frameworks were re-joined using conventional soldering procedures. The one screw test was used when assembling prosthetic frameworks to the implants. An optical microscope with precision of 0.001 mm was used to measure the marginal misfit at the prosthetic abutment/implant interface. The measurements were analyzed before and after the soldering/welding procedures in each group. The analyses were performed in three points of each faces: V, L and D at each implant. Marginal misfit averages (µm) were calculated for each face and each framework in both groups after soldering/welding.Results were treated with Mann-Whitney test (p<0.05). Mean fit values (in µm) before soldering process were equal to zero for both groups. After soldering processes were performed, it was observed that, in group 1 the mean vertical misfit medium value were 12µm as long as in group 2 the mean values were 38µm. Within the limits of this study it was possible to conclude that the laser welding procedure may provide a more accurate fit between implants and Co-Cr prosthetic frameworks compared to the conventional soldering technique.